The Democratic Republic of Congo: Endeavoring Women Empowerment after a War of Rape - Meutia, Deni (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2018)
This paper analyzed the use of rape as a weapon in Democratic Republic of Congo conflict zone. Rape usually used by the arm group to weaken their enemy. This strategy did not only targeted to women but also men. Rape gave different effect toward women and men. The purpose of this paper is to explain how rape become the weapon of conflict and their effect to the victims, even men and woman. Feminist perspective used in this paper. In the end, the author found that women have a way to overcome the effect and impact of rape better than men do. Social structure, which placed men in the upper side of women, made the effect and impact on the men who experienced rape victim hard to release their suffering. Therefore, the main goal of this paper is to show how women and men could manage their self as a victim in the conflict zone.